A Comprehensive Model of Factors Associated With Subjective Perceptions of "Living Well" With Dementia: Findings From the IDEAL Study. (January 2019) - Clare, Linda; Wu, Yu-Tzu; Jones, Ian R.; Victor, Christina R.; Nelis, Sharon M.; Martyr, Anthony; Quinn, Catherine; Litherland, Rachael; Pickett, James A.; Hindle, John V.; Jones, Roy W.; Knapp, Martin; et al.
Abstract : Introduction: We aimed to better understand what predicts the capability to "live well" with dementia by identifying the relative contribution of life domains associated with the subjective experience of living well. Methods: We analyzed data from 1547 individuals with mild-to-moderate dementia in the IDEAL cohort. We generated a "living well" latent factor from measures of quality of life, satisfaction with life, and well-being. We used multivariate modeling to identify variables related to living well measures and structural equation modeling to derive latent variables for 5 life domains and to examine the associations of these domains with living well. Results: All 5 domains were individually associated with living well. When modeled together, the psychological characteristics and psychological health domain was the only independent predictor of living well [effect size, 3.55; 95% confidence interval (CI): 2.93-4.17], and effect sizes were smaller for physical fitness and physical health (1.23, 95% CI: −0.10 to 2.58), social capitals, assets and resources (0.67; 95% CI: −0.04 to 1.38), managing everyday life with dementia (0.33; 95% CI: −0.06 to 0.71), and social location (0.08; 95% CI: −2.10 to 2.26). Discussion: Psychological resources, and the social, environmental, and physical factors that underpin positive psychological states, are potentially important targets for interventions and initiatives that aim to improve the experience of living with dementia. Abstract : Supplemental Digital Content is available in the text.